Komparasi Model Struktur dengan Dua Metode (Matriks dengan Cross) - Fansuri, Subaidillah; Deshariyanto, Dwi; Diana, Anita Intan Nura (Fakultas Teknik, Universitas Wiraraja, 2025)
Analyzing the structure using different manual methods certainly has a different flow. The results of the calculation of the structural analysis of each manual method certainly have varying values. Where the analysis will compare the two manual methods, namely the matrix method and the cross method. Based on these differences, a comparative analysis is carried out between the manual method (matrix method) and other manual methods (the cross method) related to the calculation results obtained from each method. The object of study analyzed is the structural model. The analytical method used is the comparative analysis method. This analysis is focused on the comparison of the two methods, namely the matrix method and the cross method in relation to the calculation results of internal forces which will be compared the magnitude and difference as well as the level of the resulting magnitude. The results of the analysis show that the values ​​generated in the two structural analysis methods are not the same. The calculation of the difference between the results of the structural analysis of the two methods on each stem has a different difference value. Based on the frequency value, each internal force in the structural analysis has a different level of magnitude. In all structural models, there is a large difference and a small difference.